Rent sharing to control non-cartel supply in the German cement market - Joseph E. Harrington; Kai Hüschelrath; Ulrich Laitenberger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
A challenge for many cartels is avoiding a destabilizing increase in non-cartel supply in response to having raised price. In the case of the German cement cartel that operated over 1991-2002, the primary source of non-cartel supply was imports from Eastern European cement manufacturers. Industry sources have claimed that the cartel sought to control imports by sharing rents with intermediaries in order to discourage them from sourcing foreign supply. Specifically, cartel members would allow an intermediary to issue the invoice for a transaction and charge a fee even though the output went directly from the cartel member's plant to the customer. We investigate this claim by first developing a theory of collusive pricing that takes account of the option of bribing intermediaries. The theory predicts that the cement cartel members are more likely to share rents with an intermediary when the nearest Eastern European plant is closer and there is more Eastern European capacity outside of the control of the cartel. Estimating a logit model that predicts when a cartel member sells through an intermediary, the empirical analysis supports both predictions.
Keywords: L41; K21; 330; collusion; cartel; non-cartel supply; cement; distribution channels; intermediary